A Qualitative Inquiry into the Formation of Generational Cohorts: A Case of an Emerging Market - Hiram, Ting; Ernest Cyril, de Run (Researchgate, 2015)
This study use sociological theories of generations to identify generational cohorts for market segmentation. These theories are predominantly used in the West, hence little is known about their relevance in emerging markets, such as Malaysia. Past studies have mostly borrowed cohort labels from that of the U.S. sources, and assumed that their characteristics can be construed in the Malaysian context. Given the exploratory nature of the study, a qualitative approach by means of personal interview was conducted to identify the actual cohorts in Sarawak, a state in Malaysia. Specifically, major societal and historical events that Sarawakians could overtly recall due to their attachment to them during formative years were elicited. Accordingly forty-eight interviews were recorded, transcribed and content-analysed. Five cohorts were identified, and they were different from that of the U.S. sources. They were subsequently labelled as Neoteric-inheritors, Prospective-pursuers, Social-strivers, Idealisticstrugglers and Battling-lifers based on their collective experience of the events. The results show the relevance of theories of generations for market segmentation in emerging market.